The role of the human resource in improving environmental performance in economic institutions - reference to the state of Sonatrach - Safia Allaoui; Benterbeh Benterbeh; Samira Mechraoui (Dirassat Journal Economic Issue, 2020)
In this work, we tried to know the role of the human resource in the economic institution and the extent of its contribution to improving environmental performance, while highlighting the nature of environmental management activity in raising the effectiveness of environmental performance, as well as knowing the contribution of environmental performance in raising the challenge and competition between economic institutions. So we chose the Sonatrach Corporation, including its subsidiaries at the national level, as it is the main driver of the national economy, and as a sample we have identified its Sub-Directorate for Maintenance in Laghouat, which is one of the most important units of the Sonatrach Corporation, as it carries out all maintenance of the fuel transport network.In the end, we concluded that environmental performance is governed by the level of human resources culture and their awareness of the impact of environmental pollution and their responsibility to reduce it. Therefore, this dimension should be taken care of and given great importance. The government and local government bodies are only members of society working in these institutions who classify development decisions, and that they control Above all, their cultures and beliefs can be directed to the positive environmental aspects, as they were not satisfied with the economic and social benefits that lead them and the state as a result of implementing this system.